2015
DOI: 10.1016/j.neuropsychologia.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stereo disparity on the behavioural and electrophysiological correlates of perception of audio–visual motion in depth

Abstract: Motion is represented by low-level signals, such as size-expansion in vision or loudness changes in the auditory modality. The visual and auditory signals from the same object or event may be integrated and facilitate detection. We explored behavioural and electrophysiological correlates of congruent and incongruent audio-visual depth motion in conditions where auditory level changes, visual expansion, and visual disparity cues were manipulated. In Experiment 1 participants discriminated auditory motion direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
(99 reference statements)
1
6
2
Order By: Relevance
“…Importantly, we found a significant interaction for visual congruence with stimulation dimension in experiment 1 (detection): RTs were shorter for visually congruent stimulation in pseudo-3D sessions than in real-3D sessions. This is in obvious contrast to some previous research: e.g., González et al (2010) suggested that disparity is an effective cue for motion perception in depth and Harrison et al (2015) even observed that facilitation effects appear to be stronger in real-3D environments than in experimental set-ups without 3D stimulation. However, in comparison to Harrison et al (2015) we did not use a discrimination task for auditory motion direction and did not focus on accuracies but rather a detection task with RTs.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Importantly, we found a significant interaction for visual congruence with stimulation dimension in experiment 1 (detection): RTs were shorter for visually congruent stimulation in pseudo-3D sessions than in real-3D sessions. This is in obvious contrast to some previous research: e.g., González et al (2010) suggested that disparity is an effective cue for motion perception in depth and Harrison et al (2015) even observed that facilitation effects appear to be stronger in real-3D environments than in experimental set-ups without 3D stimulation. However, in comparison to Harrison et al (2015) we did not use a discrimination task for auditory motion direction and did not focus on accuracies but rather a detection task with RTs.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in obvious contrast to some previous research: e.g., González et al (2010) suggested that disparity is an effective cue for motion perception in depth and Harrison et al (2015) even observed that facilitation effects appear to be stronger in real-3D environments than in experimental set-ups without 3D stimulation. However, in comparison to Harrison et al (2015) we did not use a discrimination task for auditory motion direction and did not focus on accuracies but rather a detection task with RTs. Possibly, a more pronounced congruence effect in a 3D environment depends on a task which requires the in-depth analysis of spatial properties and is only reflected in answer quality but not in reaction speed during temporal detection.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The stimulus used in the experiment contained no stereo disparity and used only two monocular cues to depth. A recent study reported that a sound moving in depth had a greater impact on detection of visual motion in depth when the visual stimulus contained stereo disparity (Harrison et al, 2015). Similarly, congruent vestibular cues had a more robust effect on perception of heading from optic flow when visual stimuli contained stereo disparity, compared to only 2D information (Butler et al, 2011).…”
Section: Discussionmentioning
confidence: 96%